Prediction of Future Streamflow for Kurau River Sub-basin by using Hydrological Modeling, HEC-HMS - Fakaruddin, Fegi Jahira; Mohd Arish, Nur Aini; Hamidon, Nuramidah (Progress in Engineering Application and Technology, 2020)
Climate change can lead to changes in the global hydrological cycle through rising surface temperatures, evaporation rates and increasing precipitation rates in some continents. Due to these changes, the flow regimes will affected by altering the magnitude and timing of the streamflow. The objectives of this study are to develop hydrological model for Kurau River Sub-basin and predict the streamflow for next 30 years (2020-2050) by using predicted future rainfall data using Hydrologic Engineering Centre-Hydrologic Modelling System (HEC-HMS). Different of data sets were performed for the calibration and validation process. A performance assessment of the developed hydrological model derived using HEC-HMS yields a correlation coefficient R2 near to 1.It showed that the HEC-HMS was reliable model to predict the hydrological changes. The simulated peak discharge was 113.7m3/s. The scenarios of excess rainfall and extremely lack of rainfall were simulated and it showed the peak discharge of Kurau River Sub-Basin decreased by 79.33% while for the excess rainfall scenario, the peak discharge was increased by 379%. Hence, this paper outlined that the climate change has the biggest impact on the magnitude of streamflow. Further research has to be continued in order to identify the cause of peak flood risk in the Kurau River catchment.